Die dimensies van kommunikasieklimaat in die formele organisasie - Sonja Verwey (Communicare)
THE purpose of this study was to identify the dimensions of communication climate. To achieve this purpose a theoretical construct in respect of communication climate, based on a literature survey, was finalised. A questionnaire covering the various dimensions of this theoretical construct was then drawn up. The questionnaire was completed by a sample of 250 people within a single organization. The main dimensions of communication climate as measured by the questionnaire were isolated by means of factor and item analyses. The results of these analyses confirmed the nature of the conceptual construct to a high extent. The questionnaire did not however succeed in identifying all dimensions. To alleviate the shortcomings of this study, a number of re- commendations for further research are made.